AN EFFECT OF PARENT’S SUPPORT ON SUCCESS OF GIVING TREATMENT AUTISM THERAPY - Fadilah, Risydah; Parinduri, Sari Atika; Pratiwi, Indah Dina; Sari, Ditya Indria (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Autism is a pervasive developmental disorder that thoroughly interferes with cognitive, emotional and psychomotor functions. Therefore it can also be said as a neurobiological disorder accompanied by several problems, such as autoimmunity, digestive disorders, sensory integration disorders and imbalance of amino acid composition. Being a parent who has an autistic child is not easy, both emotionally and financially. There are even parents who have to sell goods that they have to cover the cost of therapy that is not cheap and is long-term. The hope is that the child will get the best chance of healing so that they will get the right knowledge about the condition of the child so that they have the right plan for their future, but this can be achieved if there is support from parents for the healing process of their child through treatment. the therapy they provide at autism therapy sites. Parent’s support in this case includes emotional, informational, instrumental, appreciation and social support. The sample used as subjects in this study were 22 parents who had autism children from various therapeutic sites in North Sumatra. The sampling technique in this study was purposive sampling where the sample of his parents were those who had given autism therapy treatment for 5 years after his child was diagnosed by a doctor or psychologist. The results of this study indicate that the influence of the support of parents who have autistic children on the success of the treatment of autism therapy that has been done.